DC and RF Performance of an N-channel Monolayer Black Phosphorus Nanoribbon Transistor - Alam, Khairul (Journal of Electronics and Electrical Engineering, 2023)
Two-dimensional black phosphorus is a relatively new discovery. There are numerous studies on black phosphorus two-dimensional transistors that focus on analog and Radio Frequency (RF) performance. However, the RF performance of black phosphorus nanoribbon transistors is yet to be explored. We use a four-band tight binding Hamiltonian in conjunction with a non-equilibrium Green's function quantum transport simulator to investigate both the Direct Current (DC) and RF performance of a monolayer black phosphorus nanoribbon transistor. We found that electron intra-band tunneling is responsible for current flow in the off-state, while in the on-state, the electrons flow over the top of the channel barrier potential. With a VDD of 0.4 V and a gate length of 5 nm, our black phosphorus nanoribbon transistor has DC performance metrics of 510 μA/μm on-state current, 105 on/off current ratio, and 65 mV/dec inverse subthreshold slope. The device's RF performance characteristics are as follows: cut-off (unity current gain) frequency of 772.84 GHz, maximum oscillation (unity power gain) frequency of 1.15 THz, and open circuit voltage gain of 26.7 dB with transistor operating in the on-state. The RF performance of the device is found to be significantly impacted by the source and drain contact resistances. With source and drain resistances set to zero, the cut-off frequency increases to 995.23 GHz and the unity power gain frequency increases to 4.16 THz. The device shows unconditional stability above 893 GHz and it is conditionally stable below this frequency.